OXIDIZING PROCESSES IN BLOOD AND AORTA OF HAMSTERS IN THE CONDITIONS OF DESIGN OF PEROXIDATIVE ATEROARTERIOSCLEROSIS’ MODEL AT CHRONIC INTOXICATION BY SODIUM NITRATE - Schirov, A.V.; Mischenko, A.V. (World of Medicine and Biology, 2012)
In an experiment it is educed on 30 goldish Syrian hamsters, that chronic intoxication of nitrate of sodium is accompanied by the increase of products superoxide anion-radical microsomal and mitohondrial electronno-transport chains of cells of aorta, activating of processes of peroxidic oxidization of lipids and diminishing of antioxidantic potential in blood of hamsters, that creates pre-conditions for development of atherosclerotic damage of vessels. It is educed, that at peroxidic ateroarteriosclerosis in the conditions of chronic intoxication nitrate of sodium is activate peroxidization of lipids substantially, that carries the decompensated character.